2016
DOI: 10.1055/s-0036-1593879
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiome and the Liver: The Basics

Abstract: The relationships between the microbiota and other aspects of normal human biology continue to be explored. Indeed, the volume of information relating to the interplay between the host and the microbiota has grown exponentially-especially with the advent of ever-improving techniques for rapidly sequencing and identifying bacterial populations and their functions. The gut is initially sterile at birth and colonization and dynamic changes occur during infancy and early childhood in order to establish a mature mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 78 publications
(104 reference statements)
0
4
0
Order By: Relevance
“…Parenthetically, it must be noted that the concept of a microbiota-gut-brain axis (and, indeed, a microbiota-gut-liver-brain axis) is far from new and was well described over 50 years ago in seminal studies on the pathogenesis of hepatic encephalopathy (HE) which identified the centrality of the gut microbiota to the genesis of this syndrome and described the beneficial impact of an intervention that modified gut bacterial population; a poorly absorbed antibiotic, on the symptoms of this syndrome [ 26 , 27 ]. Indeed, the model developed to explain the pathophysiology of HE; namely, the convergence of small intestinal bacterial overgrowth (SIBO) and/or an abnormal microbiota, impaired gut barrier function, a pro-inflammatory state and the appearance in the systemic circulation of neuro-active molecules generated by bacterial metabolism has become virtually ubiquitous in relation to most disorders where a role for the microbiota-gut-brain axis has been invoked [ 28 ] ( Figure 1 ).…”
Section: The Microbiota-gut-brain Axismentioning
confidence: 99%
“…Parenthetically, it must be noted that the concept of a microbiota-gut-brain axis (and, indeed, a microbiota-gut-liver-brain axis) is far from new and was well described over 50 years ago in seminal studies on the pathogenesis of hepatic encephalopathy (HE) which identified the centrality of the gut microbiota to the genesis of this syndrome and described the beneficial impact of an intervention that modified gut bacterial population; a poorly absorbed antibiotic, on the symptoms of this syndrome [ 26 , 27 ]. Indeed, the model developed to explain the pathophysiology of HE; namely, the convergence of small intestinal bacterial overgrowth (SIBO) and/or an abnormal microbiota, impaired gut barrier function, a pro-inflammatory state and the appearance in the systemic circulation of neuro-active molecules generated by bacterial metabolism has become virtually ubiquitous in relation to most disorders where a role for the microbiota-gut-brain axis has been invoked [ 28 ] ( Figure 1 ).…”
Section: The Microbiota-gut-brain Axismentioning
confidence: 99%
“…Microbiological bile analysis from patients with SC-CIP and primary sclerosing cholangitis (PSC) showed an altered microbiological profile in these two groups, with predominance of drug-resistant organisms in the bile of SC-CIP [ 14 ]. Data on the gut microbiome in SC-CIP is not available to date, but other chronic liver diseases have distinct changes in microbiome composition with potential impact on inflammation (non-alcoholic fatty liver disease (NAFLD), alcoholic liver disease, PSC and cirrhosis) [ 15 , 16 , 17 , 18 ]. Altered gut microbiome composition is thought to increase intestinal permeability [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is most commonly seen in cirrhosis but was also described in alcohol-induced injury, NAFLD and hepatits C virus (HCV)-mediated liver injury [ 20 , 21 , 22 , 23 , 24 ]. When gut permeability is increased, bacteria from the intestinal lumen can translocate into extraintestinal locations of the body (lymph nodes, blood) and trigger inflammatory reactions, leading to disease progression [ 16 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…2 ). The mature microbiome might drive inflammation in liver disease and governs tolerance to these bacteria [ 53 ]. The gut associated lymphoid tissue [ 51 ] (GALT) scans microbiata composition:, portal blood reaching the liver will be processed at least in part, by immune recognition.…”
Section: Introductionmentioning
confidence: 99%